Antara Kesejahteraan Buruh dan Sustainability Dunia Usaha, dalam RUU Cipta Tenaga kerja Omnibus Law - Mahayoni Mahayoni (Problematika Hukum, 2019)
Demonstrations against Law No.11 of 2020 concerning Job Creation are rife. But is it true that workers / laborers or students and other protesters already know and understand the contents of Law No.11 of 2020 concerning Job Creation correctly? Is it true that the law only benefits entrepreneurs and for the sake of attracting foreign investors, and neglecting the welfare of workers / laborers? So far, Law Number 13 Year 2003 concerning Manpower has become a solid guideline for the industrial world in Indonesia. Is it considered to be more pro-workers? Is the presence of Law No.11 of 2020 concerning Job Creation which has been passed by the DPR no longer siding with workers? This study will compare in detail the Job Creation Law and Law No. 13/2013 on Manpower from the labor / labor side and the business continuity side. So that both parties can understand each other and together build a strong economy. Entrepreneurs must be given the opportunity to develop and sustain, while workers’ / laborers' welfare is very decisive in the progress of the company. The author examines by comparing 9 things that are the differences in the two laws. The author compares the verses related to workers' rights that they have felt and enjoyed. The author analyzes the things that benefit or harm the worker / laborer or entrepreneur. Thus, it is hoped that this researc